Neuroscientific therapies for atrial fibrillation. Issue 7 (14th May 2021) - Hanna, Peter; Buch, Eric; Stavrakis, Stavros; Meyer, Christian; Tompkins, John D; Ardell, Jeffrey L; Shivkumar, Kalyanam
Abstract: The cardiac autonomic nervous system (ANS) plays an integral role in normal cardiac physiology as well as in disease states that cause cardiac arrhythmias. The cardiac ANS, comprised of a complex neural hierarchy in a nested series of interacting feedback loops, regulates atrial electrophysiology and is itself susceptible to remodelling by atrial rhythm. In light of the challenges of treating atrial fibrillation (AF) with conventional pharmacologic and myoablative techniques, increasingly interest has begun to focus on targeting the cardiac neuraxis for AF. Strong evidence from animal models and clinical patients demonstrates that parasympathetic and sympathetic activity within this neuraxis may trigger AF, and the ANS may either induce atrial remodelling or undergo remodelling itself to serve as a substrate for AF. Multiple nexus points within the cardiac neuraxis are therapeutic targets, and neuroablative and neuromodulatory therapies for AF include ganglionated plexus ablation, epicardial botulinum toxin injection, vagal nerve (tragus) stimulation, renal denervation, stellate ganglion block/resection, baroreceptor activation therapy, and spinal cord stimulation. Pre-clinical and clinical studies on these modalities have had promising results and are reviewed here.